(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2022)
The application of comprehensive quality management and the best leadership style must be followed by Implementing elements of the management accounting system, one of which is the performance measurement system because it can help achieve strategic goals and short-term goals of the company. This study aims to analyze the influence of the application of total quality management and leadership style on the financial performance of Islamic Commercial Banks in Ambon City. The data analysis method used is Partial Least Squares (PLS). The sample of this study was employees who worked for Islamic banks in Ambon City. The results showed that total quality management and leadership style had a positive effect on financial performance. Keywords: total quality management, leadership style, financial performance